พรุน:ผลไม้เพื่อสุขภาพ Prunes : Fruit for Health - คงสมบูรณ์เวช, ศัลยา (Journal of The Royal Thai Army Nurses, 2012)
บทคัดย่อ พรุนหรือพลัมแห้งเป็นผลไม้ที่ถูกจัดว่าเป็นหนึ่งในอาหารเพื่อสุขภาพ ซึ่งอุดมไปด้วยสารอาหารที่ให้ประโยชน์ต่อสุขภาพ สารอาหารที่พบมากในพรุนได้แก่ คาร์โบไฮเดรตเชิงซ้อนที่มีดัชนีน้ำตาลต่ำ มีวิตามินและแร่ธาตุที่สำคัญ มีสารต้านอนุมูลอิสระ สารพฤกษเคมีและใยอาหาร แต่มีพลังงานต่ำ สารพฤกษเคมีที่สำคัญในพรุนคือ สารฟีนอลในรูปกรดนีโอคลอโรจีนิค และคลอโรจีนิค ซึ่งมีฤทธิ์ต้านอนุมูลอิสระ ช่วยในการป้องกันโรคเรื้อรัง สารประกอบฟีนอลมีผลในการช่วยลดอุบัติการณ์เกิดโรคหัวใจ โดยการป้องกันแอลดีแอลคอเลสเทอรอลถูกทำปฏิกิริยาออกซิเดชั่น พรุนเป็นที่รู้จักกันมานานว่าเป็นยาระบายธรรมชาติที่ดี เนื่องจากมีใยอาหารสูงช่วยในการส่งเสริมสุขภาพระบบย่อย นอกจากนี้ใยอาหารยังช่วยลดความเสี่ยงมะเร็ง งานวิจัยที่ผ่านมารายงานว่า พรุนมีองค์ประกอบที่เป็นยาธรรมชาติ ซึ่งให้ผลในการลดระดับน้ำตาล ลดไขมัน ลดความดันโลหิต ป้องกันกระดูกพรุน ซึ่งได้กล่าวถึงในบทความนี้ คำสำคัญ: พรุน สารต้านอนุมูลอิสระ โรคหัวใจและหลอดเลือด โรคกระดูดพรุน ยาระบาย Abstract Prunes or dried plums are considered as one of the functional foods contains nutrient-dense composition, which provide many health benefits. They contain substantial amounts of complex carbohydrates with low glycemic index, important vitamins and minerals, antioxidants, phytochemicals, and fibers for a small amount of calories. The very important phytochemical in prunes are phenolic compounds, mainly neochlorogenic and chlorogenic acids, which function as antioxidants and contribute to preventing many chronic diseases. Phenolic compounds have been found to associate with lowered incidence of heart disease by protecting low-density lipoprotein (LDL or “bad" cholesterol) from oxidation. The well-known natural-laxative effect of prune is attributed to the high fiber content of prunes contributing to digestive health. High-fiber intake is also associated with decreased cancer risk. Accumulated studies also showed that prunes contain therapeutic components that produce effect on anti-hyperglycemic, anti-hyperlipidemic, anti-hypertensive, and anti-osteoporosis which are discussed. Key words: Prunes, Anti-oxidant, Cardiovascular diseases, Osteoporosis, Laxative